Oral Dysbiosis in Severe Forms of Periodontitis Is Associated With Gut Dysbiosis and Correlated With Salivary Inflammatory Mediators: A Preliminary Study - Kawamoto, Dione; Borges, Rodrigo; Ribeiro, Rodolfo Alvarenga; de Souza, Robson Franciso; Amado, Pâmela Pontes Penas; Saraiva, Luciana; Horliana, Ana Carolina Ratto Tempestini; Faveri, Marcelo; Mayer, Marcia Pinto Alves (Frontiers in Oral Health, 2021)
Inflammation is a driven force in modulating microbial communities, but little is known on the interplay between colonizing microorganisms and the immune response in periodontitis. Since local and systemic inflammation may play a whole in disease, we aimed to evaluate the oral and fecal microbiome of periodontitis patients and to correlate the oral microbiome data with inflammatory mediator’s levels in saliva. Methods: Nine stage 3/grade B periodontitis patients (P) and 9 age matched non-affected controls (H) were evaluated. Microbial communities of oral biofilms (supra and subgingival from affected and non-affected sites) and feces were determined by sequencing analysis of 16SrRNA V3–V4 region. Salivary levels of 40 chemokines and cytokines were correlated with oral microbiome data. Results: Supragingival microbial communities of P differed from H (Pielou´s evenness index, and Beta diversity, Weighted UniFrac), since relative abundance (RA) of Defluviitaleaceae, Desulfobulbaceae, Mycoplasmataceae, Peptostreococcales-Tissierellales and Campylobacteraceae was higher in P, whereas Muribaculaceae and Streptococcaceae were more abundant in H. Subgingival non affected sites of P did not differ from H, except for a lower abundance of Gemellaceae. The microbiome of affected periodontitis sites (PD≥ 4mm) clustered apart from subgingival sites of H. Oral pathobionts were more abundant in sub and supragingival biofilms of P than H. Fecal samples of P were enriched with Acidaminococcus, Clostridium, Lactobacillus, Bifidobacterium, Megasphaera and Romboutsia when compared to H. IL-6 and inflammatory chemokines salivary levels were positively correlated with RA of several recognized and putative pathobionts, whereas RA of beneficial species such as Rothia aeria and Haemophilus parainfluenzae was negatively correlated with levels of CCL2, which is considered protective. Dysbiosis in periodontitis patients was not restricted to periodontal pockets but was also seem in supragingival and subgingival non-affected sites and in feces. Subgingival dysbiosis revealed microbial signatures characteristic for different immune profiles, suggesting a role for candidate pathogens and beneficial organisms in the inflammatory process of periodontitis.